Exploring patient-centered barriers to hemophilia care in Southern Nigeria: Study Protocol - Eguzo K; Ekwere T; Kirikareye B; Okoye H; Egharevba P; Oluoha C (Ibom Medical Journal)
Background: Hemophilia is a rare, inherited bleeding disorder which affects about three out of every one million Nigerians. Evidence shows that most PLwH in Nigeria do not know enough about the condition and face some barriers. The goal of this paper is to describe the study protocol used to develop and validate tools that would explore the barriers and knowledge gaps related to hemophilia, as a part of a larger needs assessment study.